JEES 2020
DOI: 10.7176/jees/10-6-11
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Solid Waste Management Strategies in Nigeria

Abstract: The global population and increased urbanization have resulted in the increased production of municipal solid waste, thus, becoming a critical issue as a result of its poor management and inappropriate disposal. This is particularly the case of developing countries. This study assessed Solid Waste Management (SWM) strategies commonly adopted by different state waste management Authorities in Nigeria with a view to develop a sustainable roadmap for the management of solid waste in Nigeria. It assessed the Tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Concerning the perception of dumpsite location and operational activities, the respondents expressed the need to locate dumpsites close to every bus stop to ease disposal (71%). A study by Nwosu & Chukwueloka, [16] expressed the need for the strategic location of dumpsites. They reported that proper designation of dumpsites in strategic locations promoted good solid waste management by 20% in studied locations in Umuahia and Enugu.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the perception of dumpsite location and operational activities, the respondents expressed the need to locate dumpsites close to every bus stop to ease disposal (71%). A study by Nwosu & Chukwueloka, [16] expressed the need for the strategic location of dumpsites. They reported that proper designation of dumpsites in strategic locations promoted good solid waste management by 20% in studied locations in Umuahia and Enugu.…”
Section: Discussionmentioning
confidence: 99%
“…For sustainable MSWM to be achieved, the various stages and processes comprising waste generation, namely sorting, segregation, characterization, storage, collection, transfer and transportation, treatment or processing, and disposal, must be effective and operational [89,90]. However, the current practice of MSWM in Nigeria is contrary to the above, as the waste generated is not segregated, and the waste collected is group together and disposed of at dumpsites without treatment [18].…”
Section: Current Practicementioning
confidence: 99%
“…In Nigeria, approximately 3.8 million tons of the 32 million tons of MSW generated annually are plastic. However, only a fraction of plastic waste is collected and recycled (Ogechukwu et al 2020). Recycling enables the reuse of plastic waste for the production of new products, enabling `a circular economy (Abdulkarim et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, most machines are expensive and bulky and therefore difficult to transport from one location to another. The crusher made by Ogechukwu et al (2020) required manual cutting of the tip of plastic bottles before feeding while the shredding machine developed by Edke et al (2020) was designed and customized for a particular type of plastic. The crusher developed by Olukanni et al (2020) was big and heavy, about 200 kg, requiring two electric motors to function efficiently.…”
Section: Introductionmentioning
confidence: 99%